An Analysis of Language Varieties Used by English Teachers in Young Learners Classes - Isry Laila Syathroh (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2018)
One of competences which teachers should possess is strategic competence. In the classes of English Language Teaching (ELT), teachers must be able to communicate either verbally or non-verbally with students to stimulate them to learn English effectively. This paper attempts to shed some light on language varieties used by English teachers in English to Young Leaners (EYL) classes. The language variation investigated is specified into the way how teachers give instruction, according to Holmes (1993), which is grouped into three categories: descriptive sentences, imperative sentences and interrogative sentences. On the ground of doing this study, two EYL teachers were involved. Since this research employs qualitative research design, the data for this study were gained through direct observation and teacher reflective notes. The study revealed that imperative sentences dominate the expressions used by teachers in EYL classes followed by questions and declarative sentences. Total Physical Response (TPR) is still assumed to be the most effective way to teach English to young learners.